Analisis Pengukuran Kinerja Dan Tingkat Partisipasi Anggota Koperasi Redelong Organik (Reo) Di Kabupaten Bener Meriah Provinsi Aceh - Mujiburrahmad Mujiburrahmad; Suyanti Kasimin; Ira Manyamsari; Ayu Lestari (JURNAL AGRIBISNIS TERPADU, 2021)
Analysis of Performance Measurement and Participation Level of Members of Organic Redelong Cooperative (REO) In Bener Meriah Regency, Aceh Province. The role of cooperatives in economic development can be realized with the active role of members in each cooperative business activity. This study aims to analyze the performance of cooperatives, the benefits of social, economic, and the level of participation of cooperative members. The method of data analysis uses the Developmental Ladder Assessment (PTP) method based on indicators of vision, capacity, networks, and resources. The results of the analysis using PTP showed that the cooperative's performance is in the green zone, the indicator of the network is in the yellow zone. From the Analysis of Ladder Assessment Development, it can be seen that cooperative performance is in good condition. The social, economic, and level of participation are high categories. Through a correlation test using Rank Spearman, information can be obtained that there is a direct relationship between social and economic benefits with the participation of members in the field of organization, capital, and business units.